Community based medical education: Prospects and challenges - Marahatta, SB (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i3.2722 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 194-195